L’évaluation environnementale stratégique dans les pays en voie de développement : le rôle des Agences multilatérales de développement - Ghislain Mwamba Tshibangu; Marcelo Montaño (VertigO)
The Multilateral Development Agencies (MDAs) have been identified as stimulating and encouraging the application of Strategic Environmental Assessment (SEA) as a requirement for lending. In the context of these corporations, this tool arose from the limitations of the Environmental Impact Assessment and changes in funding policies. SEA was first regulated by the World Bank in 1999, followed by the African Development Bank and the Asian Development Bank respectively in 2001 and 2003 and finally by the Inter-American Development Bank in 2007. The analysis of MDAs environmental policies reveals similarities regarding the environmental assessment related to funding requests. The present paper recognizes the role of MDAs in the dissemination of SEA in developing countries and reports an overview of the SEAs required by development corporations to inform their decisions. Results show an increasing number of SEA applications over time and reveal that the first applications of this instrument intervened before its formal adoption by the MDAs. A narrow focus of the energy sector reveals that the hydropower stands out as the sub-sector that has received the largest number of SEAs. The article concludes suggesting a characterization of SEAs applied to this sub-sector given its impacts and importance within MDAs.